ANALISIS BUTIR SOAL TES URAIAN UJIAN TENGAH SEMESTER MATA KULIAH STATISTIK - Eko Agustiawan; Anies Fuady; Sunismi (Educare : Jurnal Ilmu Pendidikan, 2023)
Statistics courses are courses that require thought processes to describe or analyze data in the form of numbers. Therefore, an assessment instrument for the statistics course test needs to be made. This study aims to determine the characteristics of the items using Anates version 4 in the form of a description test document which totals 4 questions. This study uses a descriptive quantitative approach method. The results showed that: the results of the analysis of the validity of the UTS essay questions in the statistics subject were valid question categories with 2 items showing a very significant correlation. The results of the reliability analysis show that the correlation coefficient is 0.65. This indicates the reliability of the item has a category of questions with high reliability. At the difficulty level, 1 item is included in the easy category (74%), 2 items are included in the moderate category (53%) and 1 item is included in the very difficult category (14%). Meanwhile, the results of the analysis of the differentiating power of the items showed that the discriminating power was sufficient, amounting to 1 item and 3 items showing good discriminating power.